EVALUATION OF STRATEGIES FOR SUCCESSFUL PROJECT MANAGEMENT IN NIGERIA - Okoro, Okechukwu Agha (Advanced Journal of Environmental Sciences (AJES), 2023)
This work is on evaluation of strategies for successful project management in Nigeria. The objectives were to; determine the effects of inflation on Public Sector projects, ascertain the effect of poor project management on public sector projects and determine the effect of unsupportive government policies on public sector projects in Nigeria. The population of this study is made up of some selected companies in Nigeria. The sampling method used for the study is convenience sampling with a sample size of 100 companies. The retrieved copies of questionnaire were analyzed using simple percentage and frequency count with the aid of the software SPSS version 20. The results of the study revealed that price inflation does significantly affect variation of construction contracts in Nigeria, also that poor management does significantly affect variation of construction contracts in Nigeria and lastly that unsupportive government policies do significantly affect variation of construction contracts in Nigeria. The study concluded that projects are the final tools used to implement strategies. It was recommended among other things that it is crucial for stakeholders to implement strategies to mitigate the impact of inflation on construction projects. This could involve conducting thorough market analyses to anticipate potential price fluctuations, negotiating fixed-price contracts where feasible, and incorporating escalation clauses in contracts to account for inflationary pressures.